Confidential Information and the Right to Freedom of Speech - Bevz, Svitlana; Tereshchuk, Oleksandr; Kravchuk, Oleksiy; Yehorova, Valentyna; Bodnarchuk, Inna; Danevych, Mykola (International Journal of Criminology and Sociology, 2021)
The article is devoted to the problem of ensuring balance in the realization of two fundamental human rights and freedoms in a democratic society – the right to freedom of speech and privacy. It has been concluded that the rights to freedom of speech and privacy are recognized as fundamental human rights that do not conflict with each other but are intangible, inherent in every person. The right to freedom of journalism is a continuation of the right to freedom of speech and information and consists in the collection, storage, and dissemination of socially important information through the mass media. The usage of the rights in question, including in the mass media actions, may not be grounds for restricting or violating the right of everyone to privacy, the confidentiality of correspondence, correspondence, telephone conversations, and entails criminal liability in cases provided by law. In the public interest, the law provides grounds for exempting a journalist from criminal liability for disclosing confidential information, in particular in the case of disclosure of information of public interest or has already been published in other media, or concerns officials of public authorities.